Reorientation of regulation to accommodate the status of online driver workers - Christiyono, Thomas Carlo; Tohari, Mohamad; Suryandari, Wieke Dewi (International Journal Labs, 2024)
The gig economy, marked by the rise of digital platforms such as ride-hailing services, has transformed labor relationships, challenging traditional employment regulations. This study examines the legal ambiguity surrounding the employment status of online motorcycle taxi drivers in Indonesia, focusing on the elements of work, wages, and command that align with employment relationships yet remain categorized as partnerships. The lack of regulatory clarity undermines drivers’ access to essential rights such as fair wages, social security, and health protections, exacerbating power imbalances and exposing them to exploitation. This research employs a normative legal method to analyze the regulatory gaps in existing labor laws and proposes a reorientation of regulations to better accommodate online drivers’ status and protect their rights. Findings highlight the need for clear legal definitions, limits on freedom of contract, and regulatory frameworks that ensure drivers’ participation in policy-making. By recognizing drivers as workers, this study advocates for a fairer, more sustainable labor framework, enhancing legal certainty and fostering trust in the digital transportation industry. Future research is suggested to explore comparative worker classification models, the economic impact of worker recognition, and the role of technology in mitigating power imbalances between drivers and platforms.